Implementasi Sistem Transmisi Gambar Menggunakan Teknologi OFDM Berbasis Software Defined Radio dengan Perangkat USRP - Prihantono Prihantono; I Gede Puja Astawa; Tri Budi Santoso (BRILIANT: Jurnal Riset dan Konseptual, 2025)
In this decade, Orthogonal Frequency Division Multiplexing (OFDM) technology has been widely applied in various modern wireless communication systems.  OFDM is used to provide high-speed data transmission that is resistant to multipath interference and offers relatively high spectrum efficiency. In this study, an OFDM system prototype equipped with a Huffman Encoder and Decoder, Convolutional Coder, and Viterbi decoder was developed. The OFDM system that has been created is implemented using a Universal Software Radio Peripheral (USRP) device to transmit image data. From the test results, it was found that the OFDM system that has been created and implemented using USRP is capable of transmitting image data well. From visual observation, there were no errors in receiving the transmitted image data. The image received at the receiver was the same shape and size as the image transmitted by the transmitter. The received image was clear, with no image defects such as scratches or mosaics at the measurement distance. A Signal to Noise Ratio (SNR) of more than 30 dB was obtained under line of sight conditions with a measurement distance of 60 cm between the transmitter and receiver. The SNR decreased gradually with increasing measurement distance, reaching approximately 27 dB at a measurement distance of 300 cm between the transmitter and receiver.